Quintrione: A new selective herbicide for weed control in rice (Oryza sativa L.). (March 2021) - Peng, Yajun; Cheng, Xiaomei; Liu, Ducai; Liu, Xueyuan; Ma, Guolan; Li, Sifu; Yang, Yuting; Zhang, Yuping; Bai, Lianyang
Abstract: Weeds present a serious problem in rice paddy fields and severely affect rice ( Oryza sativa L.) quality and yield. Quintrione is a new herbicide developed for use in rice. It inhibits p-hydroxyphenylpyruvate dioxygenase and regulates hormone levels to control weeds. In 2014–2016, field plot trials were conducted to evaluate the control efficacies of quintrione at different application rates and times against barnyardgrass, Echinochloa crus-galli (L.) P.Beauv., climbing seedbox, Ludwigia prostrata Roxb., and sheathed monochoria, Monochoria vaginalis (Burm. f.) C.Presl. Its phytotoxic effects on rice were compared with those of pretilachlor, penoxsulam and metamifop in Changsha, China. Quintrione, under the tested conditions, caused various levels of phytotoxicity in rice when applied 3 days after sowing (DAS) only. However, greater than 90% control efficacies against barnyardgrass were achieved by quintrione at 300 g a.i. ha −1  at 3 DAS, 450 g a.i. ha −1  at early post-emergence (EPOST) and 600 g a.i. ha −1  at early tillering (ET), against climbing seedbox at all the tested application rates and times, and against sheathed monochoria at 3 DAS only. Quintrione had a greater control efficacy against climbing seedbox and a similar efficacy against barnyardgrass compared with pretilachlor, penoxsulam and metamifop. Quintrione showed significantly greater, similar and lower efficacies against sheathed monochoria than metamifop, pretilachlor and penoxsulam, respectively. In addition, the rice yields after quintrione treatments were greater than, or similar to, those after pretilachlor, penoxsulam and metamifop treatments. Thus, quintrione appears to be an effective herbicide to control barnyardgrass and climbing seedbox in rice paddies when used at EPOST and ET stages. Highlights: Good control of climbing seedbox and barnyard grass by quintrione at all times. Quintrione provided poor control of sheathed monochoria except when applied 3 DAS. No phytotoxicity was observed on rice when quintrione applied at EPOST and ET. Quintrione gave better control of climbing seedbox than contemporary agents. Quintrione could be an important rotated herbicide for resistant weeds management.